A multi-layer composite anti-counterfeiting film and preparation method thereof
By fusing fluorescence and photochromic properties in the anti-counterfeiting film, using semi-step emulsion polymerization and electrospinning technology, a multi-layer composite anti-counterfeiting film was prepared, which solved the problem of easy replication of traditional anti-counterfeiting films and single anti-counterfeiting effect, and realized the Stronger anti-counterfeiting effect and application value.
Patent Information
- Application Number
- CN202411416946.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-11
AI Technical Summary
Traditional anti-counterfeiting films rely on a single technology, are easy to be copied and have a single anti-counterfeiting effect, making it difficult to effectively protect consumer rights.
The preparation method of multi-layer composite anti-counterfeiting film is adopted to fuse fluorescence and photochromic properties, and the colloidal microsphere components are prepared by semi-step emulsion polymerization. Perovskite quantum dots are added to form a photonic crystal film, and electrospinning technology is used. A photochromic film layer is formed on its surface, combining a composite liquid component of polypyrrole and phosphomolybic acid.
It improves the anti-counterfeiting effect of the anti-counterfeiting film, enhances the performance of fluorescence and structural color rendering, enriches optical performance, and enhances the application value of the anti-counterfeiting film.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of anti-counterfeiting films, and in particular to a multi-layer composite anti-counterfeiting film and a preparation method thereof. Background Art
[0002] In the context of today's rapid development of the market economy, product anti-counterfeiting has become an important means to protect consumer rights and maintain market order. With the continuous advancement of science and technology, counterfeit and shoddy goods are becoming increasingly rampant, causing huge losses to companies and consumers. Therefore, it is particularly important to develop efficient and reliable anti-counterfeiting technology. Fluorescence and photochromic properties are two important anti-counterfeiting methods. They are widely used in the field of anti-counterfeiting due to their unique visual effects and difficult-to-copy characteristics.
[0003] Traditional anti-counterfeiting films mostly rely on a single anti-counterfeiting technology, such as laser holography and precision printing. These technologies have improved the anti-counterfeiting effect to a certain extent, but they still have shortcomings such as being easy to copy and having a single anti-counterfeiting effect. If the fluorescence and photochromic properties can be combined to prepare an anti-counterfeiting film, the anti-counterfeiting effect of the anti-counterfeiting film can be greatly improved. Summary of the invention
[0004] Technical issues solved
[0005] In view of the above-mentioned shortcomings of the prior art, the present invention provides a multi-layer composite anti-counterfeiting film and a preparation method thereof, and prepares an anti-counterfeiting film with better anti-counterfeiting effect by integrating fluorescence and photochromic properties.
[0006] Technical Solution
[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0008] A method for preparing a multi-layer composite anti-counterfeiting film, the preparation method comprising:
[0009] S1, using styrene, n-butyl acrylate, methacrylic acid and allyl methacrylate as raw materials, a semi-stepwise emulsion polymerization method was used to prepare the colloidal microsphere component;
[0010] S2, adding 3%-5% of the weight of perovskite quantum dots to the colloidal microsphere component, dispersing them evenly and then casting them into a clean polytetrafluoroethylene mold, and drying the obtained film to be recorded as a photonic crystal film;
[0011] S3, compounding polypyrrole and phosphomolybdic acid to prepare a composite liquid component, and then adding the composite liquid component to a polylactic acid spinning solution to prepare a photochromic spinning solution;
[0012] S4. The photochromic spinning solution is electrospinned on the surface of the photonic crystal film to form a photochromic film layer, and the obtained layer is a multi-layer composite anti-counterfeiting film.
[0013] Furthermore, the preparation method of the colloidal microsphere component in S1 is:
[0014] S1.1, 90g of deionized water, 9g of sodium polyoxyethylene fatty alcohol ether sulfate, 155g of styrene, 160g of n-butyl acrylate, 7g of methacrylic acid and 16g of allyl methacrylate were poured into a flask, stirred at a speed of 500r / min for 30min, and the result was recorded as a pre-emulsion; 1g of ammonium persulfate was dissolved in 14g of deionized water, and the result after stirring and dissolving was recorded as an ammonium persulfate solution;
[0015] S1.2. Pour 160g of deionized water into an empty flask under nitrogen protection, heat to 87°C, add 0.6g of ammonia water, then add 13g of pre-emulsion and 14g of ammonium persulfate solution, stir at 200r / min for 10min, then drop the remaining pre-emulsion, 8g of ammonium persulfate solution and 10g of 10% ammonia solution, keep warm at 87°C for 1h, the result is recorded as the reaction system;
[0016] S1.3. Add 7 g of ammonium persulfate solution to the reaction system, then continue to keep the temperature at 87°C for 1 hour, then cool to 40°C and add 10% ammonia solution by mass to adjust the pH value to 7.5, cool to room temperature again and filter through a 200-mesh sieve. The filtrate obtained is the colloidal microsphere component.
[0017] Furthermore, the specific operation of stirring and dissolving in S1.1 is stirring at a rotation speed of 500 r / min for 10 min, and the dripping rate in S1.2 is 2 drops / s.
[0018] Furthermore, the preparation method of the perovskite quantum dots in S2 is:
[0019] S2.1. Weigh 0.7 g of lead bromide and 1.2 g of cesium bromide and add them to 100 mL of N,N-dimethylformamide, then add 4 mL of oleic acid and 8 mL of oleylamine, and stir at a constant temperature of 90°C and a speed of 300 r / min for 5 min. The result is recorded as the mixed component;
[0020] S2.2, add 100 mL of toluene to the mixed components, stir and centrifuge, remove the upper layer, then add 150 mL of ethyl acetate, stir and centrifuge again, remove the upper layer, and record the result as the precipitate component;
[0021] S2.3. Add 100 mL of cyclohexane to the precipitated component, then stir at 300 r / min for 10 min and let stand at room temperature for 48 h. Pour off the upper liquid and vacuum dry the lower precipitate. Grind it through a 200-mesh sieve to obtain perovskite quantum dots.
[0022] Furthermore, the specific operation of stirring and centrifuging in S2.2 is stirring at a speed of 500 r / min for 5 minutes and then centrifuging at a speed of 6000 r / min for 5 minutes, and the specific operation of stirring and centrifuging again in S2.2 is stirring at a speed of 500 r / min for 10 minutes and then centrifuging at a speed of 6000 r / min for 5 minutes.
[0023] Furthermore, the specific operation of uniform dispersion in S2 is stirring at a speed of 200 r / min for 10 minutes, the specific operation of drying in S2 is drying in a constant temperature blast drying oven at 60° C. for 10-20 minutes, and the thickness of the photonic crystal film in S2 is 10-20 μm.
[0024] Furthermore, the preparation method of the composite liquid component in S3 is:
[0025] 0.02 g of polypyrrole was dispersed in 20 mL of N,N-dimethylformamide, and the mixture was stirred at 300 r / min for 10 min to obtain a polypyrrole solution. 0.04 g of phosphomolybdic acid was dispersed in 20 mL of anhydrous ethanol, and the mixture was stirred at 300 r / min for 10 min to obtain a phosphomolybdic acid solution. The polypyrrole solution and the phosphomolybdic acid solution were mixed, and the mixture was stirred at 500 r / min for 5 min to obtain a composite liquid component.
[0026] Furthermore, the preparation method of the photochromic spinning solution in S3 is:
[0027] S3.1, dichloromethane and N,N-dimethylformamide are mixed in a volume ratio of 2:1 to prepare a solvent component, and then polylactic acid is added in an amount of 10% by weight of the solvent component, and the mixture is stirred at a speed of 500 r / min for 10 min to obtain a polylactic acid spinning solution;
[0028] S3.2, adding 8-10 parts by volume of the composite liquid component into 50 parts by volume of the polylactic acid spinning solution, stirring at a speed of 500 r / min for 10 minutes to obtain the photochromic spinning solution.
[0029] Furthermore, the spinning voltage of electrospinning in S4 was 15 kV, the working distance of electrospinning was 13 cm, and the solution flow rate of electrospinning was 1 mL / h.
[0030] A multi-layer composite anti-counterfeiting film is prepared by a method for preparing the multi-layer composite anti-counterfeiting film.
[0031] Beneficial Effects
[0032] The present invention provides a multi-layer composite anti-counterfeiting film and a preparation method thereof. Compared with the prior art, the present invention has the following beneficial effects:
[0033] 1. The colloidal microsphere component prepared by the semi-stepwise emulsion polymerization method using styrene, n-butyl acrylate, methacrylic acid and allyl methacrylate as raw materials has excellent structural stability and dispersibility. Perovskite quantum dots are added in the process of preparing photonic crystal films using the colloidal microsphere component, and the perovskite quantum dots can be embedded in the photonic crystal film formed by the colloidal microspheres, so that the periodic structure of the photonic crystal interacts with the fluorescence characteristics of the perovskite quantum dots, thereby enhancing fluorescence. Secondly, the colloidal microspheres act as a protective layer to wrap the perovskite quantum dots inside, reducing The direct contact between quantum dots and the external environment reduces their erosion by factors such as water, oxygen, light, and heat, improves the stability of quantum dots, and prevents the agglomeration of perovskite quantum dots, maintaining their uniform distribution state, which helps maintain their optical properties. Finally, the photonic crystal film itself has the characteristics of structural color rendering, that is, light of a specific wavelength is reflected back within the photon bandgap to form a specific color, and the fluorescence emission of perovskite quantum dots can provide another source of color. The combination of the two makes the prepared film have the dual properties of structural color rendering and fluorescence, enriching the optical performance of the film.
[0034] 2. Polypyrrole has a protonation function. After being compounded with phosphomolybdic acid, it can interact with non-chemical bond-type lactam bonds to promote protonation, thereby improving the photochromic performance and broadening the light absorption range. Under visible light irradiation, this composite component can change from colorless to blue and show good reversibility. The composite liquid component prepared by compounding polypyrrole and phosphomolybdic acid is added to the polylactic acid spinning solution to form a photochromic spinning solution. A photochromic film layer is formed on the surface of the photonic crystal film by an electrospinning method. The prepared photochromic film layer can have excellent biodegradability. Combined with the fluorescent properties of the photonic crystal film itself, the prepared multi-layer composite anti-counterfeiting film can have the function of anti-counterfeiting color change on both sides, thereby enhancing the application value of the anti-counterfeiting film in the anti-counterfeiting field to a certain extent. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] The present invention will be further described below in conjunction with the embodiments.
[0037] Example 1
[0038] A method for preparing a multi-layer composite anti-counterfeiting film in this embodiment is as follows:
[0039] S1, using styrene, n-butyl acrylate, methacrylic acid and allyl methacrylate as raw materials, a semi-stepwise emulsion polymerization method was used to prepare the colloidal microsphere component;
[0040] The preparation method of the colloidal microsphere component in S1 is:
[0041] S1.1, 90g of deionized water, 9g of sodium polyoxyethylene fatty alcohol ether sulfate, 155g of styrene, 160g of n-butyl acrylate, 7g of methacrylic acid and 16g of allyl methacrylate were poured into a flask, stirred at a speed of 500r / min for 30min, and the result was recorded as a pre-emulsion; 1g of ammonium persulfate was dissolved in 14g of deionized water, and stirred at a speed of 500r / min for 10min, and the result was recorded as an ammonium persulfate solution;
[0042] S1.2. Pour 160g of deionized water into an empty flask under nitrogen protection, heat to 87°C, add 0.6g of ammonia water, then add 13g of pre-emulsion and 14g of ammonium persulfate solution, stir at 200r / min for 10min, then add the remaining pre-emulsion, 8g of ammonium persulfate solution and 10g of 10% ammonia solution at a rate of 2 drops / s, keep warm at 87°C for 1h after the addition is completed, and the result is recorded as the reaction system;
[0043] S1.3. Add 7 g of ammonium persulfate solution to the reaction system, then continue to keep the temperature at 87°C for 1 hour, then cool to 40°C and add 10% ammonia solution by mass to adjust the pH value to 7.5, cool to room temperature again and filter through a 200-mesh sieve. The filtrate obtained is the colloidal microsphere component.
[0044] S2, adding 3% of the weight of perovskite quantum dots to the colloidal microsphere component, dispersing them evenly and then casting them into a clean polytetrafluoroethylene mold, and drying the obtained film to be recorded as a photonic crystal film;
[0045] Among them, the preparation method of perovskite quantum dots in S2 is:
[0046] S2.1. Weigh 0.7 g of lead bromide and 1.2 g of cesium bromide and add them to 100 mL of N,N-dimethylformamide, then add 4 mL of oleic acid and 8 mL of oleylamine, and stir at a constant temperature of 90°C and a speed of 300 r / min for 5 min. The result is recorded as the mixed component;
[0047] S2.2, add 100 mL of toluene to the mixed components, stir at a speed of 500 r / min for 5 min, centrifuge at a speed of 6000 r / min for 5 min and remove the supernatant, then add 150 mL of ethyl acetate, stir at a speed of 500 r / min for 10 min, centrifuge at a speed of 6000 r / min for 5 min and remove the supernatant, the result is recorded as the precipitated component;
[0048] S2.3. Add 100 mL of cyclohexane to the precipitated component, then stir at 300 r / min for 10 min and let stand at room temperature for 48 h. Pour off the upper liquid and vacuum dry the lower precipitate. Grind it through a 200-mesh sieve to obtain perovskite quantum dots.
[0049] The specific operation of uniform dispersion in S2 is stirring at a speed of 200 r / min for 10 min. The specific operation of drying in S2 is placing in a constant temperature blast drying oven at 60° C. for 10 min. The thickness of the photonic crystal film in S2 is 10 μm.
[0050] S3, compounding polypyrrole and phosphomolybdic acid to prepare a composite liquid component, and then adding the composite liquid component to a polylactic acid spinning solution to prepare a photochromic spinning solution;
[0051] Wherein, the preparation method of the composite liquid component in S3 is:
[0052] 0.02 g of polypyrrole was dispersed in 20 mL of N,N-dimethylformamide, and the mixture was stirred at 300 r / min for 10 min to obtain a polypyrrole solution. 0.04 g of phosphomolybdic acid was dispersed in 20 mL of anhydrous ethanol, and the mixture was stirred at 300 r / min for 10 min to obtain a phosphomolybdic acid solution. The polypyrrole solution and the phosphomolybdic acid solution were mixed, and the mixture was stirred at 500 r / min for 5 min to obtain a composite liquid component.
[0053] The preparation method of the photochromic spinning solution in S3 is:
[0054] S3.1, dichloromethane and N,N-dimethylformamide are mixed in a volume ratio of 2:1 to prepare a solvent component, and then polylactic acid is added in an amount of 10% by weight of the solvent component, and the mixture is stirred at a speed of 500 r / min for 10 min to obtain a polylactic acid spinning solution;
[0055] S3.2, adding 8 parts by volume of the composite liquid component into 50 parts by volume of the polylactic acid spinning solution, stirring at a speed of 500 r / min for 10 minutes to obtain the photochromic spinning solution.
[0056] S4. The photochromic spinning solution is electrospinned to form a photochromic film layer on the surface of the photonic crystal film, and the result is a multi-layer composite anti-counterfeiting film. Among them, the spinning voltage of the electrospinning in S4 is 15 kV, the working distance of the electrospinning is 13 cm, and the solution flow rate of the electrospinning is 1 mL / h.
[0057] A multi-layer composite anti-counterfeiting film is prepared by a method for preparing the multi-layer composite anti-counterfeiting film.
[0058] Example 2
[0059] A method for preparing a multi-layer composite anti-counterfeiting film in this embodiment is as follows:
[0060] S1, using styrene, n-butyl acrylate, methacrylic acid and allyl methacrylate as raw materials, a semi-stepwise emulsion polymerization method was used to prepare the colloidal microsphere component;
[0061] The preparation method of the colloidal microsphere component in S1 is:
[0062] S1.1, 90g of deionized water, 9g of sodium polyoxyethylene fatty alcohol ether sulfate, 155g of styrene, 160g of n-butyl acrylate, 7g of methacrylic acid and 16g of allyl methacrylate were poured into a flask, stirred at a speed of 500r / min for 30min, and the result was recorded as a pre-emulsion; 1g of ammonium persulfate was dissolved in 14g of deionized water, and stirred at a speed of 500r / min for 10min, and the result was recorded as an ammonium persulfate solution;
[0063] S1.2. Pour 160g of deionized water into an empty flask under nitrogen protection, heat to 87°C, add 0.6g of ammonia water, then add 13g of pre-emulsion and 14g of ammonium persulfate solution, stir at 200r / min for 10min, then add the remaining pre-emulsion, 8g of ammonium persulfate solution and 10g of 10% ammonia solution at a rate of 2 drops / s, keep warm at 87°C for 1h after the addition is completed, and the result is recorded as the reaction system;
[0064] S1.3. Add 7 g of ammonium persulfate solution to the reaction system, then continue to keep the temperature at 87°C for 1 hour, then cool to 40°C and add 10% ammonia solution by mass to adjust the pH value to 7.5, cool to room temperature again and filter through a 200-mesh sieve. The filtrate obtained is the colloidal microsphere component.
[0065] S2, adding 5% by weight of perovskite quantum dots to the colloidal microsphere component, dispersing them evenly and then casting them into a clean polytetrafluoroethylene mold, and drying the obtained film as a photonic crystal film;
[0066] Among them, the preparation method of perovskite quantum dots in S2 is:
[0067] S2.1. Weigh 0.7 g of lead bromide and 1.2 g of cesium bromide and add them to 100 mL of N,N-dimethylformamide, then add 4 mL of oleic acid and 8 mL of oleylamine, and stir at a constant temperature of 90°C and a speed of 300 r / min for 5 min. The result is recorded as the mixed component;
[0068] S2.2, add 100 mL of toluene to the mixed components, stir at a speed of 500 r / min for 5 min, centrifuge at a speed of 6000 r / min for 5 min and remove the supernatant, then add 150 mL of ethyl acetate, stir at a speed of 500 r / min for 10 min, centrifuge at a speed of 6000 r / min for 5 min and remove the supernatant, the result is recorded as the precipitated component;
[0069] S2.3. Add 100 mL of cyclohexane to the precipitated component, then stir at 300 r / min for 10 min and let stand at room temperature for 48 h. Pour off the upper liquid and vacuum dry the lower precipitate. Grind it through a 200-mesh sieve to obtain perovskite quantum dots.
[0070] The specific operation of uniform dispersion in S2 is stirring at a speed of 200 r / min for 10 minutes. The specific operation of drying in S2 is placing in a constant temperature blast drying oven at 60° C. for 20 minutes. The thickness of the photonic crystal film in S2 is 20 μm.
[0071] S3, compounding polypyrrole and phosphomolybdic acid to prepare a composite liquid component, and then adding the composite liquid component to a polylactic acid spinning solution to prepare a photochromic spinning solution;
[0072] Wherein, the preparation method of the composite liquid component in S3 is:
[0073] 0.02 g of polypyrrole was dispersed in 20 mL of N,N-dimethylformamide, and the mixture was stirred at 300 r / min for 10 min to obtain a polypyrrole solution. 0.04 g of phosphomolybdic acid was dispersed in 20 mL of anhydrous ethanol, and the mixture was stirred at 300 r / min for 10 min to obtain a phosphomolybdic acid solution. The polypyrrole solution and the phosphomolybdic acid solution were mixed, and the mixture was stirred at 500 r / min for 5 min to obtain a composite liquid component.
[0074] The preparation method of the photochromic spinning solution in S3 is:
[0075] S3.1, dichloromethane and N,N-dimethylformamide are mixed in a volume ratio of 2:1 to prepare a solvent component, and then polylactic acid is added in an amount of 10% by weight of the solvent component, and the mixture is stirred at a speed of 500 r / min for 10 min to obtain a polylactic acid spinning solution;
[0076] S3.2, adding 10 parts by volume of the composite liquid component into 50 parts by volume of the polylactic acid spinning solution, stirring at a speed of 500 r / min for 10 minutes to obtain the photochromic spinning solution.
[0077] S4. The photochromic spinning solution is electrospinned to form a photochromic film layer on the surface of the photonic crystal film, and the result is a multi-layer composite anti-counterfeiting film. Among them, the spinning voltage of the electrospinning in S4 is 15 kV, the working distance of the electrospinning is 13 cm, and the solution flow rate of the electrospinning is 1 mL / h.
[0078] A multi-layer composite anti-counterfeiting film is prepared by a method for preparing the multi-layer composite anti-counterfeiting film.
[0079] Example 3
[0080] A method for preparing a multi-layer composite anti-counterfeiting film in this embodiment is as follows:
[0081] S1, using styrene, n-butyl acrylate, methacrylic acid and allyl methacrylate as raw materials, a semi-stepwise emulsion polymerization method was used to prepare the colloidal microsphere component;
[0082] The preparation method of the colloidal microsphere component in S1 is:
[0083] S1.1, 90g of deionized water, 9g of sodium polyoxyethylene fatty alcohol ether sulfate, 155g of styrene, 160g of n-butyl acrylate, 7g of methacrylic acid and 16g of allyl methacrylate were poured into a flask, stirred at a speed of 500r / min for 30min, and the result was recorded as a pre-emulsion; 1g of ammonium persulfate was dissolved in 14g of deionized water, and stirred at a speed of 500r / min for 10min, and the result was recorded as an ammonium persulfate solution;
[0084] S1.2. Pour 160g of deionized water into an empty flask under nitrogen protection, heat to 87°C, add 0.6g of ammonia water, then add 13g of pre-emulsion and 14g of ammonium persulfate solution, stir at 200r / min for 10min, then add the remaining pre-emulsion, 8g of ammonium persulfate solution and 10g of 10% ammonia solution at a rate of 2 drops / s, keep warm at 87°C for 1h after the addition is completed, and the result is recorded as the reaction system;
[0085] S1.3. Add 7 g of ammonium persulfate solution to the reaction system, then continue to keep the temperature at 87°C for 1 hour, then cool to 40°C and add 10% ammonia solution by mass to adjust the pH value to 7.5, cool to room temperature again and filter through a 200-mesh sieve. The filtrate obtained is the colloidal microsphere component.
[0086] S2, adding 4% of the weight of perovskite quantum dots to the colloidal microsphere component, dispersing them evenly and then casting them into a clean polytetrafluoroethylene mold, and drying the obtained film as a photonic crystal film;
[0087] Among them, the preparation method of perovskite quantum dots in S2 is:
[0088] S2.1. Weigh 0.7 g of lead bromide and 1.2 g of cesium bromide and add them to 100 mL of N,N-dimethylformamide, then add 4 mL of oleic acid and 8 mL of oleylamine, and stir at a constant temperature of 90°C and a speed of 300 r / min for 5 min. The result is recorded as the mixed component;
[0089] S2.2, add 100 mL of toluene to the mixed components, stir at a speed of 500 r / min for 5 min, centrifuge at a speed of 6000 r / min for 5 min and remove the supernatant, then add 150 mL of ethyl acetate, stir at a speed of 500 r / min for 10 min, centrifuge at a speed of 6000 r / min for 5 min and remove the supernatant, the result is recorded as the precipitated component;
[0090] S2.3. Add 100 mL of cyclohexane to the precipitated component, then stir at 300 r / min for 10 min and let stand at room temperature for 48 h. Pour off the upper liquid and vacuum dry the lower precipitate. Grind it through a 200-mesh sieve to obtain perovskite quantum dots.
[0091] The specific operation of uniform dispersion in S2 is stirring at a speed of 200 r / min for 10 minutes. The specific operation of drying in S2 is drying in a constant temperature forced air drying oven at 60° C. for 15 minutes. The thickness of the photonic crystal film in S2 is 15 μm.
[0092] S3, compounding polypyrrole and phosphomolybdic acid to prepare a composite liquid component, and then adding the composite liquid component to a polylactic acid spinning solution to prepare a photochromic spinning solution;
[0093] Wherein, the preparation method of the composite liquid component in S3 is:
[0094] 0.02 g of polypyrrole was dispersed in 20 mL of N,N-dimethylformamide, and the mixture was stirred at 300 r / min for 10 min to obtain a polypyrrole solution. 0.04 g of phosphomolybdic acid was dispersed in 20 mL of anhydrous ethanol, and the mixture was stirred at 300 r / min for 10 min to obtain a phosphomolybdic acid solution. The polypyrrole solution and the phosphomolybdic acid solution were mixed, and the mixture was stirred at 500 r / min for 5 min to obtain a composite liquid component.
[0095] The preparation method of the photochromic spinning solution in S3 is:
[0096] S3.1, dichloromethane and N,N-dimethylformamide are mixed in a volume ratio of 2:1 to prepare a solvent component, and then polylactic acid is added in an amount of 10% by weight of the solvent component, and the mixture is stirred at a speed of 500 r / min for 10 min to obtain a polylactic acid spinning solution;
[0097] S3.2, adding 9 parts by volume of the composite liquid component into 50 parts by volume of the polylactic acid spinning solution, stirring at a speed of 500 r / min for 10 minutes to obtain the photochromic spinning solution.
[0098] S4. The photochromic spinning solution is electrospinned to form a photochromic film layer on the surface of the photonic crystal film, and the result is a multi-layer composite anti-counterfeiting film. Among them, the spinning voltage of the electrospinning in S4 is 15 kV, the working distance of the electrospinning is 13 cm, and the solution flow rate of the electrospinning is 1 mL / h.
[0099] A multi-layer composite anti-counterfeiting film is prepared by a method for preparing the multi-layer composite anti-counterfeiting film.
[0100] Comparative Example 1
[0101] The multi-layer composite anti-counterfeiting film and the preparation method thereof provided in this comparative example are substantially the same as those in Example 1, with the main difference being that the perovskite quantum dots in Example 1 are not added in this comparative example 1.
[0102] Comparative Example 2
[0103] The multi-layer composite anti-counterfeiting film and its preparation method provided in this comparative example are roughly the same as those in Example 1, with the main difference being that in this comparative example 2, the composite liquid component in Example 1 is replaced with a fluorescent small molecule material of model TPECNPy-2 purchased on the market.
[0104] Comparative Example 3
[0105] The multi-layer composite anti-counterfeiting film and its preparation method provided in this comparative example are roughly the same as those in Example 1, with the main difference being that in this comparative example 3, the composite liquid component in Example 1 is replaced with a fluorescent small molecule material of model TPECNPy-3 purchased on the market.
[0106] Performance Testing
[0107] The multi-layer composite anti-counterfeiting films prepared in Examples 1-3 and Comparative Examples 1-3 are marked as Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2 and Comparative Example 3, respectively. Then, the performance of Examples 1-3 and Comparative Examples 1-3 is tested. The specific testing methods and test items are as follows:
[0108] 1. Examples 1-3 and Comparative Examples 1-3 were immersed in anhydrous ethanol and pure water respectively, and their color change speeds were tested. If the color change occurred within 5 seconds, it was marked as fast, and if the color change occurred slower than 5 seconds, it was marked as slow. The color change speed data were recorded in the following table;
[0109] 2. The photochromic film layers of Examples 1-3 and Comparative Examples 1-3 were irradiated under natural light and 365nm ultraviolet light for 10s, respectively, and the degree of color change was detected. The degree of color change was divided into 1 to 5 levels, and 1 to 5 levels respectively indicated that the degree of color change was from small to large. The obtained data were recorded in the following table;
[0110]
[0111] It can be seen from the data in the above table that the multilayer composite anti-counterfeiting film in the present embodiments 1-3 can change color quickly when immersed in anhydrous ethanol and pure water compared with comparative examples 1-3, and the multilayer composite anti-counterfeiting film in the present embodiments 1-3 has a greater degree of color change under different light than comparative examples 1-3, indicating that adding perovskite quantum dots in the process of preparing photonic crystal film can enhance the fluorescence intensity of the anti-counterfeiting film, and also indicating that adding polypyrrole and phosphomolybdic acid to the polylactic acid spinning solution to prepare a photochromic film layer can make the anti-counterfeiting film have a more obvious degree of color change, thereby making the multilayer composite anti-counterfeiting film prepared in the present invention have better application prospects in the field of anti-counterfeiting.
[0112] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0113] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a multi-layer composite anti-counterfeiting film, characterized in that: The preparation method is: S1, using styrene, n-butyl acrylate, methacrylic acid and allyl methacrylate as raw materials, a semi-stepwise emulsion polymerization method was used to prepare the colloidal microsphere component; S2, adding 3%-5% of the weight of perovskite quantum dots to the colloidal microsphere component, dispersing them evenly and then casting them into a clean polytetrafluoroethylene mold, and drying the obtained film to be recorded as a photonic crystal film; S3, compounding polypyrrole and phosphomolybdic acid to prepare a composite liquid component, and then adding the composite liquid component to a polylactic acid spinning solution to prepare a photochromic spinning solution; S4, forming a photochromic film layer on the surface of the photonic crystal film by electrostatic spinning of the photochromic spinning solution, thereby obtaining a multi-layer composite anti-counterfeiting film; The preparation method of the colloidal microsphere component in S1 is: S1.1, 90g of deionized water, 9g of sodium polyoxyethylene fatty alcohol ether sulfate, 155g of styrene, 160g of n-butyl acrylate, 7g of methacrylic acid and 16g of allyl methacrylate were poured into a flask, stirred at a speed of 500r / min for 30min, and the result was recorded as a pre-emulsion; 1g of ammonium persulfate was dissolved in 14g of deionized water, and the result after stirring and dissolving was recorded as an ammonium persulfate solution; S1.
2. Pour 160g of deionized water into an empty flask under nitrogen protection, heat to 87°C, add 0.6g of ammonia water, then add 13g of pre-emulsion and 14g of ammonium persulfate solution, stir at 200r / min for 10min, then drop the remaining pre-emulsion, 8g of ammonium persulfate solution and 10g of 10% ammonia solution, keep warm at 87°C for 1h, the result is recorded as the reaction system; S1.3, add 7g of ammonium persulfate solution to the reaction system, then continue to keep the temperature at 87℃ for 1h, then cool to 40℃ and add 10% ammonia solution by mass to adjust the pH value to 7.5, cool to room temperature again and filter through a 200-mesh sieve, the filtrate obtained is the colloidal microsphere component; The preparation method of perovskite quantum dots in S2 is: S2.
1. Weigh 0.7 g of lead bromide and 1.2 g of cesium bromide and add them to 100 mL of N,N-dimethylformamide, then add 4 mL of oleic acid and 8 mL of oleylamine, and stir at a constant temperature of 90°C and a speed of 300 r / min for 5 min. The result is recorded as the mixed component; S2.2, add 100 mL of toluene to the mixed components, stir and centrifuge, remove the upper layer, then add 150 mL of ethyl acetate, stir and centrifuge again, remove the upper layer, and record the result as the precipitate component; S2.3, add 100 mL of cyclohexane to the precipitate component, then stir at 300 r / min for 10 min and let stand at room temperature for 48 h, pour off the upper liquid and vacuum dry the lower precipitate, grind through a 200 mesh sieve to obtain the perovskite quantum dots; The preparation method of the composite liquid component in S3 is: 0.02 g of polypyrrole was dispersed in 20 mL of N,N-dimethylformamide, and the mixture was stirred at 300 r / min for 10 min to obtain a polypyrrole solution. 0.04 g of phosphomolybdic acid was dispersed in 20 mL of anhydrous ethanol, and the mixture was stirred at 300 r / min for 10 min to obtain a phosphomolybdic acid solution. The polypyrrole solution and the phosphomolybdic acid solution were mixed, and the mixture was stirred at 500 r / min for 5 min to obtain a composite liquid component. The preparation method of the photochromic spinning solution in S3 is: S3.1, dichloromethane and N,N-dimethylformamide are mixed in a volume ratio of 2:1 to prepare a solvent component, and then polylactic acid is added in an amount of 10% by weight of the solvent component, and the mixture is stirred at a speed of 500 r / min for 10 min to obtain a polylactic acid spinning solution; S3.2, adding 8-10 parts by volume of the composite liquid component into 50 parts by volume of the polylactic acid spinning solution, stirring at a speed of 500 r / min for 10 minutes to obtain the photochromic spinning solution.
2. The method for preparing a multi-layer composite anti-counterfeiting film according to claim 1, characterized in that: The specific operation of stirring and dissolving in S1.1 is stirring at a speed of 500 r / min for 10 min, and the dripping rate in S1.2 is 2 drops / s.
3. The method for preparing a multi-layer composite anti-counterfeiting film according to claim 1, characterized in that: The specific operation of stirring and centrifuging in S2.2 is stirring at a speed of 500 r / min for 5 minutes and then centrifuging at a speed of 6000 r / min for 5 minutes. The specific operation of stirring and centrifuging again in S2.2 is stirring at a speed of 500 r / min for 10 minutes and then centrifuging at a speed of 6000 r / min for 5 minutes.
4. The method for preparing a multi-layer composite anti-counterfeiting film according to claim 1, characterized in that: The specific operation of uniform dispersion in S2 is stirring at a speed of 200 r / min for 10 minutes. The specific operation of drying in S2 is drying in a constant temperature blast drying oven at 60° C. for 10-20 minutes. The thickness of the photonic crystal film in S2 is 10-20 μm.
5. The method for preparing a multi-layer composite anti-counterfeiting film according to claim 1, characterized in that: The spinning voltage of electrospinning in S4 was 15 kV, the working distance of electrospinning was 13 cm, and the solution flow rate of electrospinning was 1 mL / h.
6. A multi-layer composite anti-counterfeiting film, characterized in that: The multi-layer composite anti-counterfeiting film is prepared by the preparation method of any one of claims 1 to 5.
Citation Information
Cited By
Photochromic film and preparation method thereof
CN120945585A
A photochromic film and a method for preparing the same
CN120945585B